PERAN MADRASAH DALAM MEMBENTUK IDENTITAS MUSLIM DI BALI - Suaidi Suaidi; Novena Ade F S (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2026)
Purpose: This study aims to investigate the strategic role of madrasas in shaping, preserving, and negotiating Muslim identity in Bali, a unique socio-cultural context dominated by Hindu majority and massive global tourism influence. Design/methodology/approach: This research employs a qualitative ethnographic approach, focusing on several madrasas in Taman Griya, Jimbaran Village, South Kuta, Badung, Bali. Data were collected through participant observation, in-depth interviews with 15 key informants (teachers, parents, students, and community leaders), focus group discussions, and documentary studies. Data analysis followed the Miles and Huberman interactive model. Research limitations/implications: This study is limited to one locality (Taman Griya, Jimbaran) over a three-month period (June-August 2024). Findings may not be generalizable to all Muslim communities in Bali without further comparative studies. Findings: The findings reveal that madrasas function as: (1) an epistemological and ideological fortress, building the foundations of aqidah, sharia, and akhlaq through a comprehensive curriculum and ritualization of daily religious practices; (2) an arena for socialization and identity affirmation, creating a safe space for symbolic expression (jilbab, Islamic greetings, dhikr) and strengthening communal solidarity; (3) a creative acculturation laboratory, facilitating dialogue between Islamic norms and Balinese local culture (e.g., Muslim attire made from endek/songket fabrics); and (4) an agent of moderation and social bridge, actively fostering harmonious relations with the Hindu community through various interfaith social programs. Originality/value: Unlike previous macro-level studies on Muslim minorities in Bali focusing on political identity or interfaith relations, this research offers a micro-ethnographic analysis of madrasas as sites of daily identity production. It demonstrates how madrasas perform cultural work—preserving, adapting, and transmitting Islamic identity—through adaptive, moderate, and contextual approaches in a minority setting.